Community-Engaged Learning in Food Systems and Public Health - Julie L. Self; Becky Handforth; Janelle Hartman; Corey McAuliffe; Elizabeth Noznesky; Rebecca J. Schwei; Laura Whitaker; Amanda J. Wyatt; Amy Webb Girard (Journal of Agriculture, Food Systems, and Community Development, 2016)
Food preferences, systems, and policies influence the health of individuals and communities both directly, through food consumption choices, and indirectly, through environmental, economic, and social impacts. To aid student understanding of these complex determinants of food choice, a student-driven, community-engaged learning course on food systems and food choices was developed. Guided by the socio-ecological model for health and the goals of the Emory Sustainability Initiative and supported by the Center for Community Partnerships (CFCP), the course objectives, curriculum, and activities were determined by the students in collaboration with the faculty advisor and community partners. Two central components of the course were student-led learning modules and community-engaged research on food systems. The four learning modules included: (1) determinants of individual food preference and choice; (2) food and agriculture systems; (3) food access and food justice; and (4) agricultural policy. Community research projects described the role of farmers' markets, community supported agriculture, conventional markets, community gardens, and farm-to-table restaurants in the production and distribution of food in metro Atlanta, with an emphasis on locally produced fruits, vegetables, meats, and milk. Where possible the projects mapped the reach of these distribution models to low-income communities and food deserts, and identified strategies to improve access to healthy food options in these communities. The course culminated in a student-organized symposium for community members and in research reports for community partners. The symposium drew diverse participants, including growers, farmers' market managers, advocacy groups, public-health scientists, policy-makers, students, and academicians. Discussions with symposium participants assisted in refining the research reports for community partners and helped identify strategies and topics for future collaborative efforts and course improvements. A grant from Emory's CFCP facilitated collaboration with community partners, community research, and dissemination of research findings.